The Use of Crossword Puzzle Learning Media to Improve Social Studies' Motivation and Learning Outcomes in Students - Ryan Shobib; Siti Azizah (SOCIALE: Jurnal Internasional Kajian Sosial, 2026)
This study is motivated by the need to improve students' cognitive learning outcomes in Social Studies (IPS), which remain below the Minimum Learning Mastery Criteria (KKTP) of 75 in class VIII-A at MTsN 1 Pamekasan. The purpose of this research is to enhance students' cognitive learning outcomes through the implementation of the Snowball Throwing learning model. The study employed a Classroom Action Research (CAR) design conducted in two cycles, involving 26 students as subjects. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through documentation, observation, and tests, and were analyzed descriptively. The success indicators were the achievement of the KKTP score of 75 and an increase in classical learning completeness. The results showed a significant improvement in student learning outcomes. In cycle I, the average score was 66.42 with a learning completeness of 38.46%. In cycle II, the average score increased to 80.15 with a learning completeness of 76.92%. These findings indicate that the Snowball Throwing learning model is effective in improving students' cognitive learning outcomes in Social Studies.